Ectomycorrhizal fungi in Eucalyptus grandis - Malvárez, G.; Major, G.; Curbelo, V.; Frioni, L. (Agrociencia Uruguay, 1997)
Mycorrhizae are symbiotic associations that make possible an active exchange of nutrients between roots and different groups of fungi. The forest species of importance in our country such as pine and eucalipt present mycorrhizae. The objectives of this work were isolate ectomycorrhizal fungi form samples obtained in pine and eucalypt forests, evaluate growth characteristics of these isolates in different growth culture media and verify the symbiotic characteristics of the isolates with eucalypt seedings and micropropagated plantules. Many isolates were obtained form sporocarps. 64% of them were identified as Pisolithus tinctorius, 27%as Scleroderma spp and the rest corresponded to species of Boletus spp and Amanita muscaria. The Sabouraud (S) and Malt Extract (ME) culture media had the best performance for the isolation while the Modified Melin Norkans (MNM) was best for maintenance. The growth studies of one native isolate showed that the growth rate was constant up to the fifth week in solid media (in S and MNM). In liquid media, the growth was more important in S medium relation to MNM (8.30 and 4.5 mg of dry mycelium/day). The culture in MNM got faster to the stationary phase due to the acidification of the media (pH 1.8) Synthesis of ectomycorrhizae was obtained between Eucalyptus seedlings and several pisolithus isolates.